Successful Treatment of Epidermal Growth Factor Receptor Inhibitor-Induced Periungual Inflammation with Adapalene - Junichi Hachisuka; Kazuko Doi; Yoichi Moroi; Masutaka Furue (Karger Publishers, 2011)
Epidermal growth factor receptor (EGFR) inhibitors are increasingly used for cancer treatment, but commonly carry dermatologic side effects. Periungual inflammation is a particularly painful condition that additionally worsens quality of life. In this paper, we report 3 cases of successful treatment of periungual inflammation induced by 3 different EGFR inhibitors (gefitinib, erlotinib, and cetuximab) with topically applied adapalene.